Drug-induced QT interval prolongation in cancer patients - Torben K. Becker; Sai-Ching J. Yeung (Frontiers Media S.A., 2011)
Cancer patients are at an increased risk for QT interval prolongation and subsequent potentially fatal Torsade de pointes tachycardia due to the multiple drugs used for treatment of malignancies and the associated symptoms and complications. Based on a systematic review of the literature, this article analyzes the risk for prolongation of the QT interval with antineoplastic agents and commonly used concomitant drugs. This includes anthracyclines, fluorouracil, alkylating agents, and new molecularly targeted therapeutics, such as vascular disruption agents. Medications used in the supportive care can also prolong QT intervals, such as methadone, 5-HT3-antagonists and antihistamines, some antibiotics, antifungals, and antivirals. We describe the presumed mechanism of QT interval prolongation, drug-specific considerations, as well as important clinical interactions. Multiple risk factors and drug-drug interactions increase this risk for dangerous arrhythmias. We propose a systematic approach to evaluate cancer patients for the risk of QT interval prolongation and how to prevent adverse effects.